APPRAISING THE SCOPE AND LIMITATIONS OF CIVIL AND CRIMINAL LIABILITIES OF TRADE UNIONS IN NIGERIA - AKIN, OGUNDAYISI OLAWALE; Olodude, A. R.; Jemialu, M.E.; Effiong, E.L. (IJRDO - Journal of Social Science and Humanities Research, 2018)
A major purpose for the creation of a trade union is the protection of furtherance of members’ common rights and interest. Trade Unions’ right are therefore necessary agents of social and economic changes in social strata. As organisations of workers formed to protect the interests that are incidental to workers’ employment are necessary agent of social economic change in the social strata. To this end, by virtue of their legal status, they are capable of suing and be sued in their registered name.  Therefore, trade unions are not totally immune from liabilities, as they can be subject to both civil and criminal liabilities as the case may be. This paper seeks to examine the categories of civil torts and criminal offences to which the unions might be held liable in the event of breaching provisions of the law or their scope of operation. Trade unionist in exceptional cases are immune from civil and criminal liabilities as provided for in the labour legislations, however, this immunities can only be accorded if the course pursued is done within the contemplation and furtherance of a trade dispute. Furthermore, this paper tends to wonder, why the incessant increase in industrial action such as strikes, as there are laws meant to put in place to regulate the spate of industrial actions particularly in Nigeria. Thus, it further recommends amongst others, the need for subsequent legislations on labour law to address the meaning of the exception clause with regards to trade unionist immunity, as this would further help in adequately defining the limit and the scope of trade unionist operations.